Beneficial and harmful effects of duloxetine versus placebo, ‘active placebo’ or no intervention for adults with major depressive disorder: a systematic review with meta-analysis and trial sequential analysis of randomised clinical trials - Christian Gluud; Marija Barbateskovic; Joanna Moncrieff; Faiza Siddiqui; Janus C Jakobsen; Mathias Maagaard; Sophie Juul; Johanne Juul Petersen; Caroline Barkholt Kamp; Mark Abie Horowitz; Kiran Kumar Katakam (BMJ Open)
Objectives To assess the beneficial and harmful effects of duloxetine versus ‘active placebo’, placebo or no intervention for adults with major depressive disorder.Design Systematic review with meta-analysis and trial sequential analysis of randomised trials.Data sources Cochrane Central Register of Controlled Trials, MEDLINE, Embase, PsycINFO and other relevant databases up until January 2023. We requested clinical study reports from 36 competent authorities.Eligibility criteria for selecting studies All randomised clinical trials comparing duloxetine versus placebo, ‘active placebo’ or no intervention, irrespective of publication type, publication status, publication year and language for treatment of major depressive disorder in adults.Data extraction and synthesis Five authors in pairs extracted data using a standardised data extraction sheet. A third review author was consulted for disagreements. Intervention effects were assessed by both random-effects and fixed-effect model meta-analyses, risk of bias assessments were performed by two independent review authors using Cochrane’s risk of bias tool V.2 and the certainty of evidence was assessed using Grading of Recommendations Assessment, Development and Evaluation.Results We included 28 trials randomising a total of 7872 participants. All results were at high risk of bias. The trials’ assessment time points were between 6 and 16 weeks after randomisation. Meta-analyses showed evidence of a beneficial effect of duloxetine on depressive symptoms (mean difference −1.81, Hamilton Depression Rating Scale (HDRS-17) points; 95% CI −2.34 to −1.28; heterogeneity I2=0.0%; 12 trials) and quality of life (mean difference −3.79 points, 95% CI −5.11 to −2.46; I2=0.0%; three trials), but the effect sizes were below our predefined minimal clinically important differences. Trial sequential analysis showed that we did not have enough information to assess the effects of duloxetine on serious adverse events (SAEs) (OR 0.67, 95% CI 0.44 to 1.02; I2=0.0%; 19 trials) or suicide or suicide attempts (OR 1.08, 95% CI 0.37 to 3.16; six trials). Duloxetine increased the risk of non-SAEs (risk ratio 1.27, 95% CI 1.22 to 1.32; I2=73.0%; 24 trials). The adverse events with the lowest number needed to harm (NNH) were nausea (NNH 6), dry mouth (NNH 13), somnolence (NNH 17), withdrawal syndrome (NNH 19), sweating (NNH 20), dizziness (NNH 21) and constipation (NNH 21).Conclusions Duloxetine appears to reduce depressive symptom scores and improve quality of life scores in the short term, but the effect sizes are minimal and of questionable patient importance. The short- and long-term effects of duloxetine on risks of SAEs and suicidality are uncertain. Duloxetine increases the risks of several short-term adverse events. Systematic assessments of benefits and harms over longer periods are required.Trial registration number PROSPERO 2016 CRD42016053931.